Customer Patronization differences and its effect on Islamic Banking Profitability - Riaz, Shakeel; Hussain, Talat (The journal of contemporary issues in business and government, 2021)
Introduction and Background: Financial intermediation is a proven function of the banking sector which advocates its growth-promoting role. But Islamic banks cover an extra mile by sharing risk and synchronizing the income of the rich and the poor. But to function smoothly, the services sector like Islamic banks must ensure that their clients/customers are patronizing them with a higher degree of engagement. A most important source of patronizing is the deposits that customers are keeping in their accounts with Islamic banks. In terms of practice, there are two types of patronizing customers.First,who places their deposits in the current account, and second who places their deposits in the saving accounts.Both of them have different expectations from the services extended by Islamic banks. Objective: The objective set by this study is to empirically evaluate whether changes in the current and saving account patronization have a role to play in Islamic banking profitability.And to determine how banks need to manage their deposit structure in order to increase the odds of profits. Design/methodology/approach: This quantitative study is based on a deductive approach and will collect the data from audited financial statements of Islamic banks for the time period from 2008 to 2018. Findings: It is expected that this study will provide the breakdown of the share of current and saving deposits for the Islamic banks, which provides the profit promoting and profit undermining shares. This breakdown will be instrumental for the policymakers to lay down a framework in managing the share of current and saving deposits in their favor. Value:Previous studies have been nosedivein providing a country-level comparison of different types of deposit to profitability. Paper Type: Research Paper